Analysis of Teacher Difficulties in Teaching Comparative Writing Using E-Learning: Analisis Kesulitan Guru dalam Pengajaran Menulis Perbandingan Menggunakan E-Learning - Tobing, Muhammad Dicky; Novitasari, Dian (Universitas Muhammadiyah Sidoarjo, 2022)
The Covid-19 pandemic has affected all aspects of life, including education. For this reason, the improvement of information technology is alternatives to help the learning process in the education sector. One such information technology is learning through the internet or can be called e-learning. With this e-learning, it is hoped that the difficulties experienced by students can be overcome during the pandemic. These difficulties include: difficulty understanding lessons, difficulty accessing the internet, concentrating difficulty, etc. On the other hand, the application of e-learning in the learning process is also an obstacle for teachers. Related to this problem, the researcher found a similar problem in a vocational school in Sidoarjo, East Java. Based on interviews conducted with one of the English teachers at the school, the obstacles experienced were: difficulty accessing the internet, and there is no internet quotas support from the school or the government that makes this online school happened.